2003
DOI: 10.1242/dev.00842
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of floral induction pathways using global expression analysis

Abstract: Flowering of the reference plant Arabidopsis thaliana is controlled by several signaling pathways, which converge on a small set of genes that function as pathway integrators. We have analyzed the genomic response to one type of floral inductive signal, photoperiod, to dissect the function of several genes transducing this stimulus, including CONSTANS, thought to be the major output of the photoperiod pathway. Comparing the effects of CONSTANS with those of FLOWERING LOCUS T, which integrates inputs from CONST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
461
0
11

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 438 publications
(498 citation statements)
references
References 76 publications
26
461
0
11
Order By: Relevance
“…GIGANTEA (GI), is an Arabidopsis clock protein that links the circadian pacemaker and the photoperiodic flowering response through interaction with COSTANT (CO) and FLOWER-ING LOCUS T (FT) (Yanovsky and Kay 2003;Mizoguchi et al 2005). Interestingly, a plant miRNA (miR-172) was identified that responds to day length (Schmid et al 2003). A recent study showed that GI regulates the response of miR-172 to change in day length (Jung et al 2007).…”
Section: Role Of Mirna In the Circadian Clockmentioning
confidence: 99%
“…GIGANTEA (GI), is an Arabidopsis clock protein that links the circadian pacemaker and the photoperiodic flowering response through interaction with COSTANT (CO) and FLOWER-ING LOCUS T (FT) (Yanovsky and Kay 2003;Mizoguchi et al 2005). Interestingly, a plant miRNA (miR-172) was identified that responds to day length (Schmid et al 2003). A recent study showed that GI regulates the response of miR-172 to change in day length (Jung et al 2007).…”
Section: Role Of Mirna In the Circadian Clockmentioning
confidence: 99%
“…In addition, LFY activates floral homeotic genes and their cofactors (Busch et al, 2001;Lamb et al, 2002;Parcy et al, 1998;Schmid et al, 2003;Weigel and Meyerowitz, 1993;William et al, 2004). These functions are generally preserved in other angiosperms, although FLO/LFY has acquired additional roles in some plants such as pea (Ahearn et al, 2001;Bomblies et al, 2003;Coen et al, 1990;Hofer et al, 1997;MolineroRosales et al, 1999;Schultz and Haughn, 1991;Souer et al, 1998;Weigel et al, 1992).…”
Section: Evolution Of Flo/lfy Genes and Body Plan In Land Plantsmentioning
confidence: 99%
“…Recent studies have uncovered the role of microRNAs (miRNAs), ~21-nucleotide noncoding RNAs, as regulators of floral patterning gene expression in Arabidopsis flower development (Aukerman and Sakai 2003;Schmid et al 2003;Achard et al 2004;Chen 2004;Mallory et al 2004a;Baker et al 2005;Millar and Gubler 2005). Plant miRNAs regulate cognate protein coding RNAs through either transcript cleavage or translational inhibition or both (reviewed in Bartel and Bartel 2003;Carrington and Ambros 2003;Bartel 2004;Dugas and Bartel 2004;He and Hannon 2004;Mallory and Vaucheret 2004;Kidner and Martienssen 2005;Chen 2005;Valencia-Sanchez et al 2006).…”
Section: Introductionmentioning
confidence: 99%